Building elder care training for migrants and refugees employed in informal care: suggestions from the SWOT analysis of the educational programme “HERO” - Finco, Matteo; Santini, Sara; Moza, Sotiria; Kyprianou, Elena; Yerou, Christina; Tsitsi, Theologia; Soulé, Maria Victoria; Charalambous, Andreas; Kassidakis, Panos; Ulecia, Julian; Pitoglou, Stavros; Galassi, Flavia (Frontiers Media S.A., 2026)
Background
The increased demand for care by older population with multimorbidity and the shortage of staff in the care sector are challenging healthcare systems across Europe. Migrants currently represent a valuable resource to bridge the gap between demand and supply of care in both the formal and informal elder care sector. Their specific educational and social needs have to be addressed by tailored training courses, which would allow them to provide quality care for older people at fair working conditions.
Methods
The study analysed the perspective of 83 migrants and refugees participating in an elder care course implemented in 2021 in Cyprus, Greece, Italy and Portugal and 35 experts in adult education and elder care, who were involved in semi-structured interviews and focus groups, respectively. The textual content were analysed thematically, to identify strengths, weaknesses, opportunities and threats of the training.
Results
Three main themes were identified that may characterise a successful and effective elder care training for migrants: useful educational content, lessons time flexibility and a meaningful relationship with the trainers. Results suggest the improvement of some educational aspects and the design of social investment policies that can recognise the acquired certification at the EU level, help trainees enter the labour market and older people have a good quality assistance.
Discussion
Proper elder care can prevent the onset of very common risks for the health of older people with long-term care needs and then decrease the hospital accesses and the general pressure on the Health System. Policy recommendations are given framed in the social investment policy framework to consider and monitor all stages of the elder care supply chain, from education up to employment of migrant care workers.